2017
DOI: 10.19082/4238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of theory-based intervention to promote physical activity among adolescent girls: a randomized control trial

Abstract: BackgroundPhysical activity (PA) rates decline among most high school female students, and due to cultural restrictions, the reduction of physical activity might be exacerbated in female Iranian adolescents.ObjectiveTo determine the effects of the physical activity education theory-based intervention to promote activity among adolescent girls.MethodsThis randomized clinical trial was conducted at public high schools in Tehran, Iran, from September 2015 to July 2016 on 578 girls. The subjects were assigned rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 30 publications
5
37
0
Order By: Relevance
“…This perception may affect their intention to change behaviours and also to change personal behaviours which require culturally sensitive knowledge translation. 41 In this study, interventions in schools and family education may contribute to successful adolescent behaviour change towards a healthy lifestyle. 41 …”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This perception may affect their intention to change behaviours and also to change personal behaviours which require culturally sensitive knowledge translation. 41 In this study, interventions in schools and family education may contribute to successful adolescent behaviour change towards a healthy lifestyle. 41 …”
Section: Methodsmentioning
confidence: 97%
“… 41 In this study, interventions in schools and family education may contribute to successful adolescent behaviour change towards a healthy lifestyle. 41 …”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the TBP, this study explores the motivational factors influencing intention and predicting attendance behaviour to a physical activity intervention. Previous studies have found support for the TPB in exploring factors involved in behavioural intention among typically developed youth in physical activity interventions (Darabi et al, 2017). Further, TPB has been widely used in understanding factors involved in behavioural intention for example, in studies on social behaviour (Hsu et al, 2017;Verma and Chandra, 2018;Zhang et al, 2017), consumer behaviour (Scalco et al, 2017) or health behaviour (Chevance et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, aspects of attitude, subjective norms, and perceived behavior control should be taken into consideration to promote one’s intention when developing strategies for behavior change. Previous interventions based on TPB have shown benign effects on increasing PA [ 19 , 20 ]. However, although TPB has provided a theoretical framework, some interventions have achieved few effects due to lack of practical techniques, and the traditional supervised PA intervention has usually suffered from high costs but relatively low popularity, low convenience, and low flexibility, as well as low anonymity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%